Possible cause of lack of positive samples on homologous blood transfusion. Issue 11 (20th October 2014) - Krotov, Grigory; Nikitina, Maria; Rodchenkov, Grigory
<x xml:space="preserve">Abstract</x> Homologous blood transfusion is a prohibited method of blood manipulation that can be used to increase the number of erythrocytes circulating in the blood stream resulting in an increased oxygen transport capacity. In doping controls, homologous blood transfusions are determined by means of a procedure based on the detection of red blood cell phenotypes by flow cytometry. In the past six years, no adverse analytical findings concerning homologous blood transfusions were reported. One explanation for that phenomenon, assuming that athletes have not completely given up this kind of manipulation, would be a more careful selection of potential donors. If such a donor has the same set of minor erythrocyte antigens as the recipient, the established methodology to detect homologous transfusion would fail. We have hypothesized that any athlete can be a potential donor for teammates with the same RhD factor and AB0 blood group. Having analyzed the phenotype of erythrocytes of 535 Russian athletes in various endurance sports, several pairs of athletes with the same phenotype were observed. Based on the frequency of occurrence of red blood cell antigens, the theoretical probability of finding a donor within a team with exactly the same phenotype was calculated, and the existing number of occurrences where two individuals share the same phenotype in the same sport was in fact five times higher than the theoretical probability. Copyright © 2014 John Wiley & Sons, Ltd.